Is There a Corporate Diversification Discount or Premium? Evidence from Chile [¿Existe Descuento O Prima de Diversificación Corporativa? Evidencia Para Chile] - Espinosa-Mendez, C (Emerald Group Publishing Ltd., 2015)
PurposeThe purpose of this paper is to analyze the effect of the corporate ownership diversification, i.e. how the involvement in the ownership of other non-financial firms affects the value of listed firms. The authors control for the unrelated diversification when the firm has different business segments in different sectors. Design/methodology/approachThe authors analyze a sample of Chilean-listed firms between 2005 and 2009, in two stages. First, the authors compute the diversification premium or discount, defined as the part of the firms’ capitalization that stems from the diversification strategy. Then, the authors regress the premium or discount against the business and ownership diversification measures and other control variables. FindingsIn addition to a discount for unrelated business diversification, the authors find an ownership diversification discount when non-financial firms are shareholders of other firms. However, this discount turns into a premium when the firm gains the control of the owned firm, especially in related sectors. Originality/valueThe authors pioneer the analysis of the ownership diversification in Latin American firms. The results apply not only to Chile but also to a number of Latin American countries since many of these countries have, in common with Chile, a concentrated corporate ownership structure and a weak protection of investors’ rights. © 2015, © Emerald Group Publishing Limited.